PEMETAAN SERTA SEBARAN SPASIAL KASUS TUBERKULOSIS DI PROVINSI ACEH - Nurfitriani Nurfitriani; Isfanda Isfanda (Jurnal Sains Riset, 2021)
Tuberculosis  caused by Mycobacterium tuberculosis (M.TB) which infects the lungs and spreads through the air. Spreading occurs that a pulmonary TB patient was coughing, sneezing or spitting, causing droplets of TB escape in the air. The exposed one will be infected easily, especially those who are immunocompromized. Aim of  this study is to identify and the spatial distribution of tuberculosis cases in Aceh during 2017-2019. Collecting the increase case of data with mapping. This research was conducted at the site of the Aceh Provincial Health Office and the Ministry of Health in June. Data obtained from the website of the Health Office and Ministry of Health of Aceh Province 2017-2018. Conclusions showed that pulmonary tuberculosis cases in Aceh Province from 2017 to 2019 were increasing in every year.Keywords: Tuberculosis, Droplet